Full-Term Baby with Cerebellar Hemorrhage Referred for Severe Jaundice Occurring within the First 3 Days of Life - In Wook Lee; Jae Kyoon Hwang; Ja-Hye Ahn; Hyun Ju Lee; Chang-Ryul Kim (Korean Society of Neonatology, 2024)
Cerebellar hemorrhage in full-term infants is a rare condition recently recognized in high-risk newborns requiring intensive care with the availability of advanced neuroimaging techniques. Several aspects such as the incidence, pathophysiology, clinical features, and prognosis of cerebellar hemorrhage in full-term infants remain unknown. We present a case of cerebellar hemorrhage with subdural hemorrhage in a patient hospitalized for jaundice after birth without a history of traumatic delivery, such as breech presentation, prolonged labor or forceps delivery. A full-term female infant weighing 3,100 g at birth, with no complications during delivery, developed jaundice within 48 hours of birth and was admitted for intensive phototherapy in the first 3 days of life with a transcutaneous total bilirubin level of 18.1 mg/dL. Magnetic resonance imaging revealed cerebellar brain lesions with a subdural hemorrhage. At the age of 3 months, the infant exhibited leg rigidity and was referred for rehabilitation. The patient showed signs of improvement during treatment and was generally catching up well with her peers at the age of 9 months. Long-term follow-ups are required to evaluate the consequences on cognitive development, behavior, and motor performance subsequently in life.